A Sociological Review of the Phenomenon of Premarital Intimacy Among Papuan Muslims in Wamena Regency - Saiful Islam; Faisal Faisal; Hendra Yulia Rahman (TATHO: International Journal of Islamic Thought and Sciences, 2026)
The aim of this qualitative study, employing a normative-sociological approach, is to identify the various social factors that contribute to the phenomenon of premarital sexual relations among Papuan Muslims in Wamena. Primary data was obtained through interviews and observation, whilst secondary data was sourced from relevant literature or documents. Analysis was conducted by relating field findings to Émile Durkheim’s theoretical framework of social behaviour. The results of the study indicate that the main factors influencing this phenomenon are weak religious education, inconsistent family control, the dominance of permissive customs, and the influence of social media and global culture. This study emphasises the importance of strengthening religious education, family supervision, and the integration of Islamic values with local wisdom as preventive measures to reduce premarital behaviour among religious communities.